BIRD-2, a BH4-domain-targeting peptide of Bcl-2, provokes Bax/Bak-independent cell death in B-cell cancers through mitochondrial Ca2+-dependent mPTP opening. (March 2021) - Kerkhofs, Martijn; La Rovere, Rita; Welkenhuysen, Kirsten; Janssens, Ann; Vandenberghe, Peter; Madesh, Muniswamy; Parys, Jan B.; Bultynck, Geert
Graphical abstract: Highlights: BIRD-2 is an IP3 R-derived peptide targeting Bcl-2's BH4 domain, thereby disrupting IP3 R/Bcl-2 complexes. BIRD-2 causes caspase-dependent cell death in diffuse large B-cell lymphoma cell lines. BIRD-2 elicits apoptotic cell death independently of the pro-apoptotic Bcl-2-family members Bim, Bax and Bak. BIRD-2-induced cell death relies on mitochondrial Ca 2+ uptake and mitochondrial permeability transition pore opening. Abstract: Anti-apoptotic Bcl-2 critically controls cell death by neutralizing pro-apoptotic Bcl-2-family members at the mitochondria. Bcl-2 proteins also act at the endoplasmic reticulum, the main intracellular Ca 2+ -storage organelle, where they inhibit IP3 receptors (IP3 R) and prevent pro-apoptotic Ca 2+ -signaling events. IP3 R channels are targeted by the BH4 domain of Bcl-2. Some cancer types rely on the IP3 R-Bcl-2 interaction for survival. We previously developed a cell-permeable, BH4-domain-targeting peptide that can abrogate Bcl-2′s inhibitory action on IP3 Rs, named Bcl-2 IP3 receptor disrupter-2 (BIRD-2). This peptide kills several Bcl-2-dependent cancer cell types, including diffuse large B-cell lymphoma (DLBCL) and chronic lymphocytic leukaemia (CLL) cells, by eliciting intracellular Ca 2+ signalling. However, the exact mechanisms by which these excessive Ca 2+ signals triggered by BIRD-2 provoke cancer cell death remain elusive. Here, we demonstrate in DLBCL that although BIRD-2 activates caspase 3/7 and provokes cell death in a caspase-dependent manner, the cell death is independent of pro-apoptotic Bcl-2-family members, Bim, Bax and Bak. Instead, BIRD-2 provokes mitochondrial Ca 2+ overload that is rapidly followed by opening of the mitochondrial permeability transition pore (mPTP). Inhibiting mitochondrial Ca 2+ overload using Ru265, an inhibitor of the mitochondrial Ca 2+ uniporter complex counteracts BIRD-2-induced cancer cell death. Finally, we validated our findings in primary CLL patient samples where BIRD-2 provoked mitochondrial Ca 2+ overload and Ru265 counteracted BIRD-2-induced cell death. Overall, this work reveals the mechanisms by which BIRD-2 provokes cell death, which occurs via mitochondrial Ca 2+ overload but acts independently of pro-apoptotic Bcl-2-family members.